The Appearance of Data - St Pierre, Elizabeth Adams (Cultural studies, critical methodologies, 2013)
This paper explores conditions that allow data to appear, to come into being, in both conventional and more radical approaches in empirical social science research. Conventional qualitative inquiry that uses a positivist ontology—even when it claims to be interpretive—treats qualitative data, words, as brute, existing independent of an interpretive frame, waiting to be “collected” by a human. However, a Deleuzo-Guattarian ontology that does not assume the subject/object binary might not think the concept data at all. The author resists recuperating data in the collapse of the old empiricism and is content to pause in the curious possibilities of a normative ontology that imagines a superior, affirmative, and experimental empiricism in which all concepts, including data, must be re-thought.